3D Subsurface Soil Deformation Data Model - Siti Nurbaidzuri, Binti Reli @ Raily; Izham, Mohamad Yusoff; Habibah, Lateh; Muhamad Uznir, Ujang (2020)
Different terrains yield different hydrological processes. Prolonged and continuous precipitation in hillslope areas contributes to the probability of slope failures. Water has the ability to shape the land where soil deformation can occur with the presence of water. Thus, the interaction between subsurface soils with water that has infiltrated the soils should be given adequate attention. This paper will introduce a new data model that integrates an environmental (hydrology and landslide), 3D Geographic Information System (3D GIS) and programming (JAVA) known as 3D Soil water Gravitational Dynamic Flow (3D-SGD Flow) data model. The 3D-SGD Flow data model combines these three main data sets as a foundation in order to provide a better simulation of soil water movement in subsurface soil, which can be used to simulate movement of terrain changes (landslide) in three-dimensional (3D) form. This paper differentiate and combines the past and present approaches and posits the newly modified approach that can be used in the future, when the drawback of each approach is improved and upgraded to fulfil the criteria to build a data model for 3D subsurface soil deformation.